Understanding groundwater storage changes and recharge in Rajasthan, India through remote sensing - Chinnasamy, Pennan; Maheshwari, B.; Prathapar, Sanmugam A. (MDPI, 2015)
Groundwater management practices need to take hydrogeology, the agro-climate and demand for groundwater into account. Since agroclimatic zones have already been demarcated by the Government of India, it would aid policy makers to understand the status of groundwater recharge and discharge in each agroclimatic zone. However, developing effective policies to manage groundwater at agroclimatic zone and state levels is constrained due to a paucity of temporal data and information. With the launch of the Gravity Recovery and Climate Experiment (GRACE) mission in 2002, it is now possible to obtain frequent data at broad spatial scales and use it to examine past trends in rain induced recharge and groundwater use. In this study, the GRACE data were used to estimate changes to monthly total water storage (TWS) and groundwater storage in different agroclimatic zones of Rajasthan, India. Furthermore, the long-term annual and seasonal groundwater storage trends in the state were estimated using the GRACE data and the trends were compared with those in rainfall data. The methodology based on GRACE data was found to be useful in detecting large scale trends in groundwater storage changes covering different agroclimatic zones. The analysis of data shows that groundwater storage trends depend on rainfall in previous years and, therefore, on the antecedent moisture conditions. Overall, the study indicates that if suitable groundwater recharge methods and sites are identified for the state, there is potential to achieve more groundwater recharge than what is currently occurring and, thus, enhancing the availability of water for irrigated agriculture.